A Pivot to Quantum: Shifting the Surveillant Assemblage - Young, Sarah; Pridmore, Jason; Brooks, Catherine (Surveillance & Society, 2025)
While much of the world focuses on artificial intelligence, quantum technologies are emerging into the technological landscape with promises to revolutionize computing, communications, and measurement, rewriting the ways that we deal with and conceptualize surveillance, privacy, and security. To avoid a future in which powerful quantum technologies shape social practices and surveillance in problematic ways, we need to begin engaging with quantum now - both as a science and its technological manifestations - to appropriately respond. While quantum discourses can be highly technical and daunting, the surveillant assemblage bridges the gap between the familiar and the future of a quantum enabled surveillance because in many ways, the surveillant assemblage is already rooted in foundations of quantum science. From this premise, we delve deeper into the surveillant assemblage’s quantum connections to argue that while quantum technologies will disrupt surveillance practices as we know it, the surveillant assemblage helps prepare for our increasingly quantum enabled surveillance futures because it attunes us to the quantum world through its provisions of 1) language and principles; 2) metaphor, and 3) technological pasts and futures.